Social and legal change in Kuria family relations - Rwezaura, Barthazar A. (1982)
This is a study of social and legal change among the Kuria people of Tanzania. It examines the transformation of the Kuria ideas and practices concerning marriage, children and property rights. The study covers a period following the colonial rule in Tanzania beginning about the turn of this century to the present. The aim of the study is to show the relationship between the integration of the Kuria economy into a world economic system and the transformation of extant social relations. Although we recognise that social change is an unceasing process in any society, this study argues that forces associated with capitalist penetration accelerated this process. Thus, for example, the authority and power of the elders who had for many generations dominated the Kuria society was undermined. There was radical transformation of kinship and property relations and elders were no longer influential in matters relating to production. There was progressive individualisation of property rights as sUbsistence production was transformed to serve the needs of the capitalist sector. The role of the law and state is also discussed. We argue that both the colonial and the post-colonial states were instrumental in this process of change even if some of their policies appear to have been aimed at conserving certain forms of traditional relations. Within this context of change the responses of the Kuria people to economic change is examined. The study argues that rather than being passive objects of capitalist penetration the Kuria tried to influence events even though their options were highly circumscribed. For the elders change represented an opportunity to utilise their traditional positions to secure resources from the non-traditional economic sector while for the younger generation and the women, change· opened up the means for them to extricate themselves from relations of subordination.